The Utilization of Internet of Things (IoT) for Multi Sensor Data Acquisition using Thingspeak - Mohamad Jamil; Muhamad Said (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
Internet Of Things (IoT) is one form of innovation that aims to expand the benefits of continuously connected internet connectivity, one example of the use of this technology is in terms of remote monitoring (eg remote monitoring); monitoring weather conditions, water levels, air pollution, forest fires and so on. In this research will apply the utilization of Internet of Things (IoT) for acquisition of multisensor measurement data using the Thingspeak interface. Based on the results of tests conducted it was found that various series of sensors, such as; temperature sensors, water level sensors, vibration sensors and smoke sensors can display data in the form of results graphs through the Thingspeak software.